Angular ranges as a reliable isokinetic method to assess shoulder rotator muscles. (October 2020) - Maryne, Cozette; Pierre-Marie, Leprêtre; Thierry, Weissland
Highlights: A novel isokinetic angular method is proposed to assess shoulder rotator muscles balance. The angular ranges method is a dynamic approach of muscle balance assessment. The angular ranges method is more finer and more reliable than classical isokinetic method usually used. The establishment of first reference values for a healthy population is proposed. Abstract: Objectives: Physiological and functional ratios of internal and external rotators are used to assess the muscle balance of shoulder joint. Ratios are usually calculated from the peak torque value (PT) of each muscle group, without taking into account the angular positions at which PT are reached. The aim of our study was to propose an alternative and reliable method based on sectorial analysis for isokinetic assessment of the shoulder muscle balance. Method: 22 men (23.0 ± 2.7y) participated in isokinetic tests of the muscle rotators in a seated position in scapular plane, at 60 °s −1, in concentric (CON) and eccentric (ECC) modes for both shoulders. Peak torque (PT) and torque averaged per range of 10° (T) were calculated for internal and external rotators. Physiological and functional ratios were calculated with classic peak approach (PT-ratios) and new sectorial approach (T-ratios). Results: PT-ratios and T-ratios were different ( P < 0.05). T-ratios were different between the angular ranges ( P < 0.05). The reliability was variable as function of angular ranges. The majority of the T-ratios calculated over non-extreme angular ranges were more reliable than PT-ratios (intraclass correlation coefficient=0.14–0.75; coefficient of variation=7.0–28.5%). Conclusions: The angular range method showed a better reliability than the peak torque method. Angular range method better reflects the functional reality because it takes into account the muscular potential in its entirety of the range of movement.